2017
DOI: 10.1186/s13012-017-0566-z
|View full text |Cite
|
Sign up to set email alerts
|

Adoption, reach, and implementation of a cancer education intervention in African American churches

Abstract: BackgroundUse of technology is increasing in health promotion and has continued growth potential in intervention research. Guided by the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework, this paper reports on the adoption, reach, and implementation of Project HEAL (Health through Early Awareness and Learning)—a community-based implementation trial of a cancer educational intervention in 14 African American churches. We compare adoption, reach, and implementation at the organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…Various studies have shown the usefulness of training community health advisors to provide psychosocial support and act as a liaison between clinicians and individuals they seek to serve [25][26][27]. By sharing similar cultural, social and economic characteristics as the populations of interest, they are more inclined to connect and understand the subtle distinctions that influence health behaviors [26].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown the usefulness of training community health advisors to provide psychosocial support and act as a liaison between clinicians and individuals they seek to serve [25][26][27]. By sharing similar cultural, social and economic characteristics as the populations of interest, they are more inclined to connect and understand the subtle distinctions that influence health behaviors [26].…”
Section: Discussionmentioning
confidence: 99%
“…While churches are promising venues for health promotion programs, [39][40][41][42] including PA interventions, 8,11,[43][44][45][46] the lack of understanding of organizational context and determinants for implementation and sustainment limit dissemination capability for these programs. Few faith-based health promotion studies have been taken to scale and 47,48 most have targeted African-American populations; 47,49,50 and only a few have targeted PA as a main outcome, with limited effectiveness. 8,45 Webb and colleagues explored faith leaders' perceptions of health and wellness; however, their sample was entirely Caucasian and majority Methodist, and did not focus on the implementation of a particular program.…”
Section: Introductionmentioning
confidence: 99%
“…While churches are promising venues for health promotion programs, 29−32 including PA interventions, 8,11,33−36 the lack of understanding of organizational context and determinants for implementation and sustainment limit dissemination capability for these programs. Few faith-based health promotion studies have been taken to scale and 37,38 most have targeted African-American populations; 37,39,40 and only a few have targeted PA as a main outcome, with limited effectiveness. 8,35 Webb and colleagues explored faith leaders' perceptions of health and wellness; however, their sample was entirely Caucasian and majority Methodist, and did not focus on the implementation of a particular program.…”
Section: Introductionmentioning
confidence: 99%